REGULATION ON SOCIAL SECURITY SYSTEM FOR WORKERS TO ACHIEVE SAFETY AND HEALTH AT WORK; COMPARISON BETWEEN INDONESIA AND MALAYSIA LABOUR LAW - Ningsih, Ayup Suran (Tadulako University, 2019)
Occupational safety and health (OSH) is a human right and an integral part of people-centered agenda for development. Safe work also underpins sustainable enterprises which benefit from improved productivity, quality, and workforce motivation. A healthy workforce and safe and productive enterprises are part of successful and sustainable development strategies. The government is obliged to protect workers through the making of public policy. The Implementation of public policy in order to protect workers is the public enactment of the rules in the field of occupational safety and health. Laws and regulations that are public are made to reduce the freedom of the individual worker and workers, so worker